Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3390/ijerph8062331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Children with Severe Fetal Alcohol Spectrum Disorders in Communities Near Rome, Italy: New Estimated Rates Are Higher than Previous Estimates

Abstract: Objective:To determine the population-based epidemiology of fetal alcohol syndrome (FAS) and other fetal alcohol spectrum disorders (FASD) in towns representative of the general population of central Italy.Methods:Slightly revised U.S. Institute of Medicine diagnostic methods were used among children in randomly-selected schools near Rome. Consented first grade children (n = 976) were screened in Tier I for height, weight, or head circumference and all children ≤10th centile on one of these measurements were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 37 publications
10
85
2
2
Order By: Relevance
“…Not only the cardinal facial features, but other facial measurements and minor anomalies are also important discriminators of FASD. Based on this study and other population-based studies, [10][11][12][13]15,16 other minor anomalies, such as those shown in Table 2, are reflected in the total dysmorphology score, which differentiates well the FASD diagnostic groups. Minor anomalies play an important role in identifying affected children.…”
Section: Physical Characteristics Of the Childrensupporting
confidence: 60%
See 2 more Smart Citations
“…Not only the cardinal facial features, but other facial measurements and minor anomalies are also important discriminators of FASD. Based on this study and other population-based studies, [10][11][12][13]15,16 other minor anomalies, such as those shown in Table 2, are reflected in the total dysmorphology score, which differentiates well the FASD diagnostic groups. Minor anomalies play an important role in identifying affected children.…”
Section: Physical Characteristics Of the Childrensupporting
confidence: 60%
“…[56][57][58][59][60][61] Recruitment of mothers to obtain maternal risk data posed significant challenges for the interviewers. Therefore, variables that differentiate maternal risk in this population were not as evident or readily obtained in this US population or in our Italian studies 15,16 as elsewhere. [23][24][25] Individualized risk for FASD via genetic and epigenetic factors may be more important to explore in this and similar middle and upper SES populations than the more generalized lower SES and childbearing risk factors of higher prevalence populations.…”
Section: Maternal Risk Measurementsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the USA, the estimated prevalence is 2e7 cases per 1000 live births [23]. Studies from Europe [24], Africa [25e27], Israel [28], Australia [29,30], and Russia [31] show a much higher prevalence. The highest prevalence to date has been reported from high-alcohol-consuming regions of South Africa (90 per 1000 births) [32].…”
Section: Fetal Alcohol Syndromementioning
confidence: 99%
“…However, in parts of France FAS and FASD prevalence rates are 1.2 and 4.8 per 1,000, respectively (Dehaene et al, 1991). FASD in Italy is estimated at 2.3% to 6.3% (May et al, 2011). Prevalence rates for FAS and PFAS in regions of Italy are even higher, ranging from 4.0 to 12.0, and 18.1 to 46.3 per 1,000 children, respectively (May et al, 2011).…”
Section: What Regions Across the World Exhibit The Highest Rates Of Fmentioning
confidence: 99%